Cyber security practitioner's guide - Jahankhani, Hamid (World Scientific, 2020)
In an era of unprecedented volatile political and economic environments across the world, computer-based cyber security systems face ever growing challenges. While the internet has created a global platform for the exchange of ideas, goods and services, it has also created boundless opportunities for cyber crime. The debate over how to plan for the cyber security of the future has focused the minds of developers and scientists alike. This book aims to provide a reference on current and emerging issues on systems security from the lens of autonomy, artificial intelligence and ethics as the race to fight and prevent cyber crime becomes increasingly pressing.